Basic Concepts of Islamic Economics - Rinda Asytuti; Amelia, Cahya; Hernawati; Aulia, Zahira Iza (International Journal of Economics (IJEC), 2025)
This study explores the foundational principles of Islamic economics, emphasizing ethical values derived from Sharia as the basis for economic activity. Unlike conventional systems that prioritize profit maximization and interest-based transactions, Islamic economics promotes justice, balance, and shared responsibility. Through a qualitative literature approach, the research examines key concepts such as ownership as a trust from God, the role of wealth in achieving social welfare, and the prohibition of riba as a means to prevent exploitation. Money is viewed not as a tradable commodity, but as a tool meant to facilitate productive and fair exchange. The study concludes that the implementation of Islamic values—particularly tawhid, justice, brotherhood, and profit-sharing-aims to establish an economy that is sustainable, equitable, and spiritually oriented